Political Communication in Britain - Mortimore, Roger. author. aut Link
XV, 349 p.
Keywords: The 2010 General Election represented a pathbreaking contest in Political Communication. The TV debates changed forever the feel of the campaign. This book brings together key commentators, analysts and polling experts to present readers with a unique and valuable insight into the development of political communication in British Politics.